Transforming Nikkeijin identity and citizenship untold life histories of Japanese migrants and their descendants in the Philippines, 1903-2013 - Ohno, Shun 1953- (Ateneo de Manila University Press, 2015)
This is an exploration of Philippine cultural history. It presents a diverse range of texts including: the legend of a mountain goddess, Pigafetta's discovery account of the Philippines, the life of a 17th-century Christian convert and the foundation narrative of a Marian shrine.